Textiles of medieval Iberia : cloth and clothing in a multi-cultural context - Owen-Crocker, Gale R.; Barrigón, María (Museum curator); Ben-Yehuda, Naḥum; Sequeira, Joana, 1985-; Fábregas, Adela; Diago Hernando, Máximo; Marín, Manuela, 1945-; Mateus, Susana Bastos; Navarro Espinach, Germán; Nogales Rincón, David (Medieval and Renaissance clothing and textiles., 2022)
An examination of the fabrics, garments and cloth of the Iberian Middle Ages, bringing out in particular the international context.